Enhanced strength and ductility of a tungsten-doped CoCrNi medium-entropy alloy. Issue 19 (14th October 2018) - Wu, Zhenggang; Guo, Wei; Jin, Ke; Poplawsky, Jonathan D.; Gao, Yanfei; Bei, Hongbin
Abstract: Abstract : Developing metallic materials with a good combination of strength and ductility has been an unending pursuit of materials scientists. The emergence of high/medium-entropy alloys (HEA/MEA) provided a novel strategy to achieve this. Here, we further strengthened a strong-and-ductile MEA using a traditional solid solution strengthening theory. The selection of solute elements was assisted by mechanical property and microstructure predictive models. Extensive microstructural characterizations and mechanical tests were performed to verify the models and to understand the mechanical behavior and deformation mechanisms of the designated CoCrNi–3W alloy. Our results show good experiment-model agreement. The incorporation of 3 at.% W into the ternary CoCrNi matrix increased its intrinsic strength by ∼20%. External strengthening through microstructural refinement led to a yield strength nearly double that of the parent alloy, CoCrNi. The increase in strength is obtained with still good ductility when tested down to 77 K. Nanoscale twin boundaries are observed in the post-fracture microstructure under 77 K. The combination of strength and ductility after W additions deviate from the traditional strength-ductility-trade-off contour.